2016
DOI: 10.1016/j.virol.2016.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Identification and subcellular localization of porcine deltacoronavirus accessory protein NS6

Abstract: Porcine deltacoronavirus (PDCoV) is an emerging swine enteric coronavirus. Accessory proteins are genus-specific for coronavirus, and two putative accessory proteins, NS6 and NS7, are predicted to be encoded by PDCoV; however, this remains to be confirmed experimentally. Here, we identified the leader-body junction sites of NS6 subgenomic RNA (sgRNA) and found that the actual transcription regulatory sequence (TRS) utilized by NS6 is non-canonical and is located upstream of the predicted TRS. Using the purifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 53 publications
2
41
0
Order By: Relevance
“…These results suggested that the NS6 protein is necessary for efficient viral replication in vivo, which may be attributable to the high pathogenicity of PDCoV. Recently, Fang et al demonstrated that the PDCoV NS6 predominantly localize to the ER complex and ER-Golgi intermediate compartment, which is the site of coronavirus assembly and packaging [29], suggesting that NS6 may be involved in virus assembly. Moreover, PDCoV NS6 was identified as an inhibitor of IFN-β expression by interacting with RIG-I and MDA5 to impede their association with doublestranded RNA, thus disturbing RLR-mediated IFN-β signal pathway [40].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These results suggested that the NS6 protein is necessary for efficient viral replication in vivo, which may be attributable to the high pathogenicity of PDCoV. Recently, Fang et al demonstrated that the PDCoV NS6 predominantly localize to the ER complex and ER-Golgi intermediate compartment, which is the site of coronavirus assembly and packaging [29], suggesting that NS6 may be involved in virus assembly. Moreover, PDCoV NS6 was identified as an inhibitor of IFN-β expression by interacting with RIG-I and MDA5 to impede their association with doublestranded RNA, thus disturbing RLR-mediated IFN-β signal pathway [40].…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, MHV and FIPV mutants bearing defective accessory protein genes were also dramatically attenuated when inoculated into their natural hosts [17,28]. Recently, PDCoV NS6, which is located between the M and N, and NS7, which is occupied within the N gene in an alternative ORF, were identified as the accessory proteins [29]. Moreover, NS7a, a 100-amino-acid-polypeptide identical to the C-terminus of NS7, has also been identified as a novel accessory protein [30].…”
Section: Introductionmentioning
confidence: 99%
“…The genome of PDCoV is composed of approximately 25.4 kb nucleotides and has a genomic organization similar to other coronaviruses: a 5′ untranslated region (UTR), open reading frame 1a (ORF1a) and ORF1b encoding two overlapping polyprotein precursors; four structural protein genes encoding spike (S), envelope (E), membrane (M), and nucleocapsid (N); three accessory protein genes encoding NS6, NS7, and NS7a; and a 3' UTR and poly (A) tail (Chen et al, 2015a;Fang et al, 2017;Fang et al, 2016;Li et al, 2014;Woo et al, 2012). For coronaviruses, the function of the S protein is to recognize receptors and mediate viral entry into host cells.…”
Section: Introductionmentioning
confidence: 99%
“…PDCoV is an enveloped, single-stranded, positive-sense RNA virus belonging to the genus Deltacoronavirus of the family Coronaviridae (4). The full-length genome of PDCoV is approximately 25.4 kb in length, with the essential genes occurring in the order 5= UTR-ORF1a/1b-S-E-M-NS6-N-NS7-NS7a-3= UTR and encoding a total of 15 mature nonstructural proteins, four structural proteins, and three accessory proteins (13,(19)(20)(21). Coronavirus accessory proteins are species specific, and each coronavirus encodes various amounts of accessory proteins interspaced between viral structural protein genes.…”
mentioning
confidence: 99%